Listy biskupa poznańskiego Ignacego Raczyńskiego z lat 1796-1798 do Jana Chrzciciela Albertrandiego - Weiss, Anzelm (Ecclesia. Studia z Dziejów Wielkopolski, 2009)
Ignacy Raczyński, the bishop of Poznań from 1794 to 1807 and then the archbishop of Gniezno, ruled the Poznań diocese in a complicated political situation that followed the loss of independence by Poland. The Poznań period of his life and activity has so far been hardly investigated. The author carries out a brief characterization of his rule in this period and publishes six of his letters to Jan Chrzciciel Albertandi, his official for the archdiaconate of Warsaw, formerly the Mazovia part of the Poznań diocese. The letters reveal a number of hitherto unknown details of the relations between the Church and the state in those times. The text also includes the pastoral letter of bishop Raczyński of 1796 to the clergy and faithful of the Poznań diocese.